Pengembangan E-Book Interaktif untuk Menunjang Pembelajaran Diferensiasi pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar - Ziaurrahman Ziaurrahman; Tabrani ZA; Andriansyah Andriansyah (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
The development of interactive e-books based on differentiation is undertaken due to the unavailability of digital learning resources, diverse learning styles among students, and a classroom environment that does not accommodate differentiated learning. The research aims to produce digital learning resources (product feasibility) and assess their effectiveness (benefits) in supporting the process of differentiated learning. The resulting product is named “E-Bid”, which is in e-Pub format, accessible on laptops, PC, and tablets, preferably connected to the internet. The research follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection methods used include tests and questionnaires. During the testing phase, two media and subject matter experts were involved. This was followed by a limited trial involving 10 fifth-grade students from Gla Meunasah Baro Elementary School to assess the level of appropriateness and usefulness of the learning outcomes in terms of differentiated learning on the topics of Hajj and Sacrifice (Kurban). The trial results showed that the product’s feasibility was rated highly, with scores of 3.44 (very feasible) from the subject matter expert and 3.57 (very feasible) from the media expert. Furthermore, the small group test received a score of 3.69 (very feasible). The assessment of the product’s benefits yielded a pre-test score of 54.3, a post-test score of 87.7, and a gain score of 33.40, indicating a highly beneficial outcome (very feasible category).